Penerapan Teknologi Digital dalam Pembelajaran Pendidikan Agama Islam - Dedy Yansyah; Dadan Sunandar; Zaenuri Zaenuri; Rian Antoni; Suci Hati (Mathematics Education Study Program, 2025)
This research aims to analyze the application of digital technology in Islamic Religious Education (PAI) learning and its impact on learning effectiveness. With the development of technology, PAI learning methods have undergone a transformation from a conventional approach to a more interactive digital-based approach. This research uses a descriptive-qualitative approach by analyzing various related literature. The research results show that the use of digital technology, such as learning applications, interactive videos, and e-learning platforms, increases students' interest in learning, deepens understanding of the material, and allows more active interaction between teachers and students. However, challenges such as limited access to technology and the readiness of teaching staff in managing digital learning are still obstacles that need to be overcome. Therefore, to optimize the use of technology in PAI learning, synergy between teachers, schools, parents and the government is needed. Teachers must improve their digital competence, schools need to provide supporting facilities, and the government must design policies that accelerate the integration of technology in the PAI curriculum. Apart from that, regulations regarding digital content used in learning must also be considered so that it remains in accordance with Islamic values.